Exogenously Applied GA3 Enhances Morphological Parameters of Tolerant and Sensitive Cyclamen persicum Genotypes under Ambient Temperature and Heat Stress Conditions - Mihaiela Cornea-Cipcigan; Mirela Irina Cordea; Rodica Mărgăoan; Doru Pamfil (Plants, 2022)
Cyclamen genus is part of the Primulaceae family consisting of 24 species widely cultivated as ornamental and medicinal plants. They also possess high plasticity in terms of adaptability to alternating environmental conditions. In this regard, the present study investigates the germination and morphological parameters of heat-tolerant and heat-sensitive Cyclamen persicum accessions in the presence of different GA3 solutions (0, 30, 70 and 90 mg/L) under ambient temperature and heat stress conditions. Heat-tolerant genotypes, mainly C3-Smartiz Victoria (6.42%), C15-Merengue magenta (6.47%) and C16-Metis silverleaf (5.12%) had the highest germination rate with 90 mg/L GA3 treatment compared with control. Regarding heat-sensitive genotypes, C11-Verano (5.11%) and C13-Metis Origami (4.28%) had the lowest values in mean germination time, along with the Petticoat genotypes C1 (73.3%) and C2 (80.0%) with a high germination percentage. Heat-tolerant genotypes positively responded to GA3 (70 and 90 mg/L) even under heat stress conditions, by their higher values in plant height, an ascending trend also seen in heat-sensitive genotypes under GA3 treatment (70 and 90 mg/L). According to the hierarchical clustering, several heat-tolerant genotypes showed peculiar behavior under heat stress conditions, namely C3 (Smartiz Victoria), C7 (Halios falbala) and C8 (Latinia pipoca) which proved to be susceptible to heat stress even under GA3 application, compared with the other genotypes which showed tolerance to higher temperatures. In the case of heat-sensitive genotypes, C4 (Smartiz violet fonce), C6 (Metis blank pur), C11 (Verano) and C13 (Metis origami) possessed higher positive or negative values compared with the other heat-sensitive genotypes with increased doses of GA3. These genotypes were shown to be less affected by heat stress, suggesting their positive response to hormone treatment. In conclusion, the above-mentioned genotypes, particularly heat-tolerant C15 and heat-sensitive C2 with the highest germination capacity and development can be selected as heat-resistant genotypes to be deposited in gene banks and used in further amelioration programs under biotic and/or abiotic stresses to develop resistant genotypes.